Menciptakan Pembelajaran Bermakna Melalui Penerapan Model Pembelajaran Berbasis Konstruktivisme - Mustika, Dea; Hidayat, Bahril; Rahmi, Laili; Oktadela, Resi; Putra, Elpri Darta; Karmelia, Karmelia; Isyara, Kayla Addina (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
It was found that teachers in elementary schools lacked training on the application of meaningful learning. Although teachers were familiar with several types of learning models, their implementation still fell short of expectations. A learning model based on constructivism theory combined with a deep learning approach could be a solution for creating meaningful learning. This activity aims to provide training to elementary school teachers on how to apply learning models based on constructivist theory with a deep learning approach in order to create meaningful learning. The learning models used as examples are the inquiry model and the learning cycle model. The activity was carried out in four stages, namely preparation, implementation, mentoring, and evaluation/follow-up. The results obtained show that the activities carried out helped provide teachers with an understanding of how to create learning with more effective and enjoyable stages. The expected follow-up is a follow-up activity in the form of training on the preparation of in-depth learning plans.